Analisa Pelaksanaan Jenjang Karir Profesional Perawat - Daniel Mada; Mira Asmirajanti; Setiawati Setiawati; Iin Inayah; Fauziah Rudhiati (Jurnal Keperawatan Silampari, 2022)
This study aims to analyze the implementation of the professional career path of nurses at the Manimeri Health Center, Teluk Bintuni Regency, West Papua Province. The research method used is qualitative research. The results obtained four themes: understanding of the career of professional nurses, the implementation of clinical authority has not been based on the career path of clinical nurses, nurses' expectations in evaluating the performance of career paths, obstacles faced in developing a professional nurse career path. In conclusion, the process of understanding the Clinical Nurse felt by the participants was not by the procedure; the career path determination process carried out at the Manimeri Health Center was not by the procedure, so the duties and authorities of each level of the Clinical Nurse should be different according to their jurisdiction, in the field implementation it is not by Clinical Nurse level, caused by the fact that every time there is a nursing action, it is not always the level of PK that should be. Keywords: Career Path, Credentials, Community Health Center Nurse